To simplify the expression (3m/4-2)+9, we first simplify the expression within the parentheses:
(3m/4-2)+9 = (3m/4 - 2) + 9
Then, we combine like terms:
= 3m/4 - 2 + 9
= (3m/4) + (9 - 2)
= 3m/4 + 7
Therefore, the simplified expression is 3m/4 + 7, not 3m/4 + 28/4.
So, the correct answer is not among the options you provided.
Simplify the following expression. (3m/4-2)+9
A. 3m+28/4
B. m+9/4
C. 3m+24/4
D. 8m/4
Please help. I got 3m/4+7 I'm not sure what I got wrong, do I use a different formula or something..?
1 answer